MEMBANGUN ETIKA DAN MORAL DALAM PROSPEK BISNIS GLOBAL SUATU TINJAUAN TEORI - Syamsu Alang (Universitas Bina Sarana Informatika, 2009)
Business constitutes one of phenomenon which happen deep the need cycle human will mark sense interaction for meeting ambition and wish to human economic activity factors it own.Business is economic activity. That don't despite activity or production activity, buy, exchange, merchant, market, work to employ, and humanity interaction another, for the purpose get gain or profit for viability and gathering adequately fund divides business agent activity performing (businessman) that own. Manner carries on business is default assess that as guidance or basis for manager and whole employee in decision making and runs ethical business. Manner and business paradigm is world different one have while it is revamped as manner paradigm concerning with business or coordinating among manner with unrealized.Regubrly admits sentral of economic viewpoint in carries on business, need shortly be added marks sense viewpoint any other again that may not be ignored, which is moral viewpoint. Good business (good business) not only business that advantages. Good business is also good business ethical ala and moral particularly enter global business prospect.Keywords : Ethics, Morality, Global Business